Expert System for Diagnosing Skin Diseases Using the Forward Chaining Method - Anindita Dhiaksa (Institute of Computer Science (IOCS), 2020)
Puskesmas is one of the most important places in daily life. The puskesmas always records and manages patient data for treatment and provides a consultation service for patients with specialist doctors. the opportunity for patients to consult for skin diseases, but this is deemed less effective, and takes a lot of time while many patients who want to seek treatment are immediately examined. To overcome this problem, a solution is given by building an Expert System for Diagnosing Skin Diseases using the Forward Chaining Method. Where this system is expected to help effectiveness in handling patient consultations and does not interfere with the time of patients queuing for treatment to be immediately treated by doctors. Consultation for patients is provided to give patients the opportunity to help identify and overcome a symptom of a disease without having to come to the puskesmas to queue and can prevent the symptoms of the disease quickly.